Peningkatan Kesadaran Halal melalui Optimalisasi Instagram pada situs @halalcorner & @halal.indonesia - Shelna Azima Azam; Amin Wahyudi; Luhur Prasetiyo (Journal of Economics, Law, and Humanities, 2025)
This study aims to explore public behavior in utilizing social media as a source of information and knowledge about halal, as well as to examine the role of social media as an agent of socialization in fostering halal awareness within society. This is a field research employing a qualitative approach through netnographic study—an interpretive method used to understand consumer behavior within virtual communities or cyberspace. The objects of study and data sources are the virtual community accounts @halalcorner and @halal.indonesia, which were observed to examine the process of transferring halal-related information and knowledge. Data were collected through digital observation, documentation, and in-depth interviews with account administrators and followers. The data analysis technique used was thematic analysis. The findings indicate that social media plays a significant role as an agent of halal socialization and contributes to shaping public awareness of halal, while also encouraging an increase in the number of MSMEs obtaining halal certification. Supporting factors for account optimization include sufficient literacy among managing teams and cross-sector collaborations. Inhibiting factors involve limited knowledge among MSMEs about halal certification, internet access issues, Instagram tool limitations, and inadequate human resources. The impacts observed include economic, social, and networking aspects.